Efeitos do tabagismo na demanda por consultas médicas - Castro, Sérgio Bastos de (2012)
This study aims to evaluate the effects of smoking on the medical appointments demand, it was used the data of Household Sample Survey - PNAD 2008 by the Brazilian Institute of Geography and Statistics - IBGE. In this work, subjects were separated into different categories: smokers (which were separated in two subcategories: intensive and non-intensive), former smokers and never smokers. It was investigated the relationship between tobacco consumption and the number of medical appointments in one year. It was used the number of medical consultations as dependent variable and variable of socioeconomic kind, health related outcomes associated with smoking and other independents. It was noted by analysis and Zero-Inflated Negative Binomial count model that was not found significant difference between smokers and never smokers on the number of medical appointments. In relation to former smokers, it was observed that these require more medical visits than those who never smoked. In addition, it was analyzed the influence of other factors in the number of queries.